Administración de costos en las pymes de transformación en la región Laja Bajío de México (2021)
This research was conducted with the purpose of determining whether the entrepreneurs of small and medium processing companies (SMEs) in Celaya (Guanajuato, Mexico) and the Laja Bajio region had put in place controls to adequately manage their production costs, analyze the elements making up those costs and define controls required to efficiently manage their costs. The study was initially exploratory and ended up being explained under a quantitative methodology. A Likert scale was developed and applied to 42 processing companies. It was determined that those SMEs entrepreneurs have not implemented the necessary administrative procedures to control their production costs. SMEs seek to pay their taxes but fail to analyze the results obtained in light of the obligations established by Mexico's tax laws. This article presents the necessary information to promote their reflection and survival.